2008
DOI: 10.1093/pcp/pcn202
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Detergent-Resistant Plasma Membrane Microdomains in Arabidopsis thaliana During Cold Acclimation

Abstract: Microdomains in the plasma membrane (PM) have been proposed to be involved in many important cellular events in plant cells. To understand the role of PM microdomains in plant cold acclimation, we isolated the microdomains as detergent-resistant plasma membrane fractions (DRMs) from Arabidopsis seedlings and compared lipid and protein compositions before and after cold acclimation. The DRM was enriched in sterols and glucocerebrosides, and the proportion of free sterols in the DRM increased after cold acclimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 89 publications
7
132
1
Order By: Relevance
“…The recent report of the role of Arabidopsis (Arabidopsis thaliana) synaptotagmin1 in the control of Begomovirus and Tobamovirus cell-to-cell movement (Lewis and Lazarowitz, 2010) sheds new light on the involvement of host membrane proteins in virus movement. Arabidopsis synaptotagmin1 resides in the cortical endoplasmic reticulum, endosomes, DIMs at the PM, and plasmodesmata (PDs; Schapire et al, 2008;Minami et al, 2009;Lewis and Lazarowitz, 2010;Yamazaki et al, 2010), and regulates endocytosis and PM repair processes (Schapire et al, 2008;Yamazaki et al, 2008;Lewis and Lazarowitz, 2010). These studies support a link between DIMs and PDs, and provide evidence for a role of DIM proteins in cell-to-cell communication via PDs.…”
Section: Implications For the Mechanisms Underlying Pvx Cell-to-cell mentioning
confidence: 74%
See 1 more Smart Citation
“…The recent report of the role of Arabidopsis (Arabidopsis thaliana) synaptotagmin1 in the control of Begomovirus and Tobamovirus cell-to-cell movement (Lewis and Lazarowitz, 2010) sheds new light on the involvement of host membrane proteins in virus movement. Arabidopsis synaptotagmin1 resides in the cortical endoplasmic reticulum, endosomes, DIMs at the PM, and plasmodesmata (PDs; Schapire et al, 2008;Minami et al, 2009;Lewis and Lazarowitz, 2010;Yamazaki et al, 2010), and regulates endocytosis and PM repair processes (Schapire et al, 2008;Yamazaki et al, 2008;Lewis and Lazarowitz, 2010). These studies support a link between DIMs and PDs, and provide evidence for a role of DIM proteins in cell-to-cell communication via PDs.…”
Section: Implications For the Mechanisms Underlying Pvx Cell-to-cell mentioning
confidence: 74%
“…Indeed, the association of Remorins with DIMs is regulated quantitatively by signals such as cold (Minami et al, 2009) and pathogen-associated molecular patterns (Keinath et al, 2010). The molecular bases of this regulation are not fully understood but may likely involve protein-protein interactions or posttranslational modifications.…”
Section: Toward Understanding the Molecular Bases Of Specific Associamentioning
confidence: 99%
“…Takahashi et al (2013) reported that the alternation of plasma membrane composition and function is one of the most important mechanisms of plant cold tolerance. A proteome profiling to characterize alternations of the Arabidopsis microdomain during cold acclimation has been conducted by Minami et al (2009) who reported the increase of clathrins and dynamin-related proteins in the microdomain during cold acclimation. Many proteins such as P-type ATPases, aquaporins and tubulins have been reported to accumulate under the effect of low-temperature treatment (Minami et al 2009;Takahashi et al 2013) (Figure 2).…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
“…71 Recent studies have provided evidence that membrane microdomains consisting of typical lipids and proteins are also present in plant cells. 72 Minami et al 73,74 revealed that detergentresistant membrane fractions prepared from cold-acclimated Arabidopsis exhibit dynamic changes in microdomain-specific lipids, sterols and glucosylceramides, and in protein profiles. These evidences strongly suggest that plasma membrane microdomains have important roles for defense and acclimation in response to environmental stresses in plants.…”
Section: Molecular Analysis Of Atbi-1-interacting Factorsmentioning
confidence: 99%